1982
DOI: 10.1083/jcb.93.3.893
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of messenger RNA-associated proteins in protein synthesis.

Abstract: Two distinct forms of globin messenger RNA were isolated from mouse spleen cells infected with Friend erythroleukemia virus: polyribosomal messenger ribonucleoprotein particles (15S mRNP), and their corresponding protein-free mRNAs obtained by chemical deproteinization . The translation efficiencies of both messenger forms were assayed in a Krebs II ascites cell-free system . Selective removal of RNA-binding proteins from the ascites cell lysate did not affect globin synthesis when the mRNA was supplied as 15S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

1983
1983
1990
1990

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…If this is the case, then the mRNA-associated proteins themselves should be able to serve as translation factors; indeed, Schmid et al reported that isolated mRNP stimulated translation in a factor-dependent cell-free trans-* Corresponding author. lation system, whereas deproteinized mRNA did not (34). This finding is the most direct evidence to date for a translational role for the proteins, and it would be conclusive except for uncertainty as to the purity of the isolated mRNP.…”
mentioning
confidence: 51%
“…If this is the case, then the mRNA-associated proteins themselves should be able to serve as translation factors; indeed, Schmid et al reported that isolated mRNP stimulated translation in a factor-dependent cell-free trans-* Corresponding author. lation system, whereas deproteinized mRNA did not (34). This finding is the most direct evidence to date for a translational role for the proteins, and it would be conclusive except for uncertainty as to the purity of the isolated mRNP.…”
mentioning
confidence: 51%
“…Bound poly(A) ÷ mRNA was eluted with low salt buffer, precipitated with ethanol and stored at -20°C for further analysis [14].…”
Section: Isolation Of Polyribosomal Mrna From Hela Cellsmentioning
confidence: 99%
“…Although mRNP proteins are hypothesized to perform roles in translational regulation, the function of most of them remain unknown (18,31,32,37,43,(54)(55)(56). To date, the four cap-binding proteins (eIF-4E and the three proteins of the eIF-4F complex) and the poly(A)-binding proteins (PABPs) are the only mRNP proteins that have been identified across species boundaries.…”
mentioning
confidence: 99%